Effect of surface topography on in vitro osteoblast function and mechanical performance of 3D printed titanium. Issue 10 (22nd March 2021) - Abar, Bijan; Kelly, Cambre; Pham, Anh; Allen, Nicholas; Barber, Helena; Kelly, Alexander; Mirando, Anthony J.; Hilton, Matthew J.; Gall, Ken; Adams, Samuel B.
Abstract: Critical‐sized defects remain a significant challenge in orthopaedics. 3D printed scaffolds are a promising treatment but are still limited due to inconsistent osseous integration. The goal of the study is to understand how changing the surface roughness of 3D printed titanium either by surface treatment or artificially printing rough topography impacts the mechanical and biological properties of 3D printed titanium. Titanium tensile samples and discs were printed via laser powder bed fusion. Roughness was manipulated by post‐processing printed samples or by directly printing rough features. Experimental groups in order of increasing surface roughness were Polished, Blasted, As Built, Sprouts, and Rough Sprouts. Tensile behavior of samples showed reduced strength with increasing surface roughness. MC3T3 pre‐osteoblasts were seeded on discs and analyzed for cellular proliferation, differentiation, and matrix deposition at 0, 2, and 4 weeks. Printing roughness diminished mechanical properties such as tensile strength and ductility without clear benefit to cell growth. Roughness features were printed on mesoscale, unlike samples in literature in which roughness on microscale demonstrated an increase in cell activity. The data suggest that printing artificial roughness on titanium scaffold is not an effective strategy to promote osseous integration.